2017
DOI: 10.1093/jxb/erx024
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of Arabidopsis arogenate dehydratases suggests novel and non-enzymatic roles

Abstract: HighlightWe show subcellular localization of all six Arabidopsis thaliana arogenate dehydratases to chloroplasts and stromules. Furthermore, ADT2 and ADT5 have additional localization patterns suggesting non-enzymatic functions and roles as moonlighting proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 94 publications
(157 reference statements)
2
23
0
Order By: Relevance
“…In addition to photobleaching, protein movement within a cell can be monitored by photoconversion of fluorescent protein from green to red fluorescence (Mathur et al, 2010;Bross et al, 2017). A striking image in which one green plastid is extending a green stromule toward another stromule that is red, which projects from a plastid containing red photoconverted mEosFP (Schattat et al, 2012a), has begun to be miscited as evidence that proteins do not flow from one plastid to another.…”
Section: Plastid Interconnections Through Stromulesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to photobleaching, protein movement within a cell can be monitored by photoconversion of fluorescent protein from green to red fluorescence (Mathur et al, 2010;Bross et al, 2017). A striking image in which one green plastid is extending a green stromule toward another stromule that is red, which projects from a plastid containing red photoconverted mEosFP (Schattat et al, 2012a), has begun to be miscited as evidence that proteins do not flow from one plastid to another.…”
Section: Plastid Interconnections Through Stromulesmentioning
confidence: 99%
“…Several different genuine plastid proteins, such as Rubisco, Asp aminotransferase (Kwok and Hanson, 2004b), cpHSP70 (Krenz et al, 2010a), NRIP1 (Caplan et al, 2015), arogenate dehydratase (Bross et al, 2017), and carbonic anhydrase (Fig. 3) have been labeled with fluorescent proteins and found to be present within stromules.…”
Section: Plastid Interconnections Through Stromulesmentioning
confidence: 99%
“…Although LALF 32-51 is much shorter than the N-terminal portion of mature 27 kDa c-zein, both sequences share an amphipathic character and contain cysteine residues, possibly initiating aggregates by hydrophobic interactions. Bross et al (2017) observed similar globular structures when they investigated localization of arogenate dehydratases (ADT) fused to cyan fluorescent protein in N. benthamiana. They postulate that the ADTs were targeted to stromules, which are stroma-filled protrusions of the outer and inner membrane from chloroplasts (Bross et al, 2017).…”
Section: Discussionmentioning
confidence: 74%
“…() observed similar globular structures when they investigated localization of arogenate dehydratases (ADT) fused to cyan fluorescent protein in N. benthamiana . They postulate that the ADTs were targeted to stromules, which are stroma‐filled protrusions of the outer and inner membrane from chloroplasts (Bross et al ., ). The similarity of these globular structures to the ones observed in our study suggests that the cTP‐LG might be targeted to stromules.…”
Section: Discussionmentioning
confidence: 77%
“…Here, the marker At5g22630 had the greatest relative centrality measure. This polymorphism represents ADT5 which has recently been suggested to moonlight proteins that play an enzymatic role in biosynthesis [72]. This same marker is also highlighted as being moderately influential in explaining the variability in allyl content across the plants (see Figure S10).…”
Section: Real Data Analysis: Arabidopsis Qtl Studymentioning
confidence: 78%